2010
DOI: 10.1021/jp100566t
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of Atomic Gold Ions: Thermochemistry for the Activation of O2 and N2O by Au+ (1S0 and 3D)

Abstract: Reaction of Au(+) ((1)S(0) and (3)D) with O(2) and N(2)O is studied as a function of kinetic energy using guided ion beam tandem mass spectrometry. A flow tube ion source produces Au(+) primarily in its (1)S(0) (5d(10)) electronic ground state level but with some (3)D and perhaps higher lying excited states. The distribution of states can be altered by adding N(2)O, which completely quenches the excited states, or CH(4) to the flow gases. Cross sections as a function of kinetic energy are measured for both neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
32
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 77 publications
9
32
0
4
Order By: Relevance
“…By observing the onset of ion chemical reactions as function of the translational energy of the ions, detailed information about the electronic state of the ion can be deduced, see e.g. [61]. Investigations of third row transition metal ions, which are the chemical homologues of 22 23 the transactinides, have shown that relativistic effects, including the actinide contraction of the valence s orbitals, lead to enhanced σ and π bonding with simple ligands, see [91].…”
Section: Ion Chemical Reactions In Buffer Gasesmentioning
confidence: 99%
“…By observing the onset of ion chemical reactions as function of the translational energy of the ions, detailed information about the electronic state of the ion can be deduced, see e.g. [61]. Investigations of third row transition metal ions, which are the chemical homologues of 22 23 the transactinides, have shown that relativistic effects, including the actinide contraction of the valence s orbitals, lead to enhanced σ and π bonding with simple ligands, see [91].…”
Section: Ion Chemical Reactions In Buffer Gasesmentioning
confidence: 99%
“…This work reveals the energetics, kinetics, and dynamics of the interaction of the rhenium metal cation with O 2 . In previous studies in our laboratory, GIBMS has been used to systematically study the kinetic energy dependent reactions of O 2 with atomic cations of the first-row, [13][14][15][16][17][18][19][20][21] second-row, 15,16,[22][23][24][25][26][27] and third-row transition metals 16,[28][29][30][31][32][33] and main group metals. [34][35][36] In many cases, analyses of the cross sections for the analogues of reaction (1) have enabled determination of the BDEs of the metal oxide cation, MO + .…”
Section: Introductionmentioning
confidence: 99%
“…Die Au-O-Bindung von 3 [AuO] + im Grundzustand kann, wie schon in früheren Arbeiten gezeigt, [11] mit einem Donor-Akzeptor-Modell beschrieben werden. Die Au-O-Bindung von 3 [AuO] + im Grundzustand kann, wie schon in früheren Arbeiten gezeigt, [11] mit einem Donor-Akzeptor-Modell beschrieben werden.…”
Section: Methodsunclassified
“…So sind in 1 2 beide Liganden über eine kovalente s(Au-C)-bzw. [3d] Dies steht im Widerspruch zu einfachen Bindungsüberlegungen mit BDE-(Cu + -O) (130 kJ mol À1 [16] ) > BDE(Au + -O) (109 kJ mol À1 [11] ); demnach sind die Ursachen der unterschiedlichen Reaktionseffizienzen komplexerer Natur und beruhen vermutlich auf detaillierteren Unterschieden zwischen den PESs beider Spezies;dies wurde auch schon für andere Systeme in einem anderen Zusammenhang diskutiert. Daher ist auch die Au-O-Bindung in 3 2 viel länger als die in 1 2 (2.17 versus 1.91 );ebenso ist auch die Au-C-Bindung leicht verlängert (2.05 i n 3 2 und 2.03 i n 1 2).…”
Section: Methodsunclassified
See 1 more Smart Citation